CANDI DAN KONTEKSNYA: TINJAUAN ARKEOLOGI-RUANG - Rangkuti, Nurhadi (Berkala Arkeologi, 1995)
Based on observations there is a pattern of the use of temple building materials at 29 sites spread across the alluvial plains and the Baturagung highlands (Ratu Boko hill area). The plateau is a source of agglomerate rocks. This type of rock was used by ancient humans for building materials for temples both on the alluvial plains and in the Baturagung plains. The research was conducted using an ecological-cultural approach that pays attention to the relationship between culture and the environment in an ecosystem.